Multimodal Coronavirus Memes: Metafunction Analysis - Damanis, Imta (Language Horizon: Journal of Language Studies, 2024)
This research aims to reveal evidence on the facts of social conditions that occur due to the coronavirus pandemic, particularly emotions of fear. This study uses a social semiotics approach. The formulation of the problem discussed is (1) What are the forms of fear in coronavirus memes, and (2) How do the coronavirus memes depict fear on the Memes app. This research uses Kress & Leeuwen's three metafunction theory and systemic functional linguistics (SFL). This research uses a qualitative descriptive method using a case study approach and is equipped with a description of the data and information obtained. The author uses books and scientific journals, the data source is downloaded from Memes Apps, and the final stage concludes the results of the analysis. Based on the results of this research, ideational, textual and interpersonal processes were found. Visual and verbal modes can make it easier for readers to capture the representation conveyed by the creator of the coronavirus meme.